Perceptions of the members of the Quezon City dental society on the effects of the Asian Economic Crisis on their dental practice - Beltran, Mary Grace C.; Poblete, Melissa A. (Adviser).
Since its onset in the early part of 1997, the Asian Economic Crisis (AEC) has devastatedly affected the Philippine economy including the private practices of dentists. The aim of this study is to now the over-all perception of the members of the Quezon City Dental Society (QCDS) on the effects of the Asia Economic Crisis on their dental practices. Approximately there are 21,628 present members of the QCDS. The research study was done during the QCDS dnetal seminars that were held last Oct. 31, 1999 and last Nov. 7, 1999. Out of the 350 questionnaires that were given out during these dental seminar, only 158 questionnaires came back completely filled up. Using the chi-square test, (a + 0.05), the observed and expected frequencies were then computed to see if there is any relationship between the number of years of dental practice and having a specialization and if it has an effect on their perceptions. Over-all, the results showed 72% of the respondents have a negative over-all perception on the effects of the Asia Economic Crisis on their dental practices. The difference between the observed and expected frequencies was not statistically significant to conclude a direct relationship of specialization and number of years of dental practice have an effect on their perceptions about the crisis.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Quezon City Dental Society; Dentistry -- Economic aspects